2018
DOI: 10.1002/pc.24909
|View full text |Cite
|
Sign up to set email alerts
|

Effect of fiber and polymer variability on the rheological properties of wood polymer composites during processing

Abstract: We investigated the effects of fiber variability, size and content on the fusion characteristics of wood particlereinforced high-density polyethylene (HDPE). Five types of wood sawdust were used: eastern white cedar, with sapwood, and heartwood treated separately; jack pine divided into wood and bark; and black spruce. Three different fiber length classes were also used. Composite pellets containing wood particles at 25, 35, and 45% by weight with HDPE were made using a corotating twin-screw extruder. The pell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 43 publications
1
15
0
Order By: Relevance
“…Consequently, during the mixing, a greater number of collisions between aggregates/agglomerates could be determined, leading to fiber deterioration [ 21 ] or even re-agglomeration phenomena [ 22 ]. It can be concluded that, at lower processing temperatures, the introduction of a greater amount of fibers determines a higher instability, physically linked to the efficiency in their incorporation into the polymer matrix [ 23 ]. However, if the mixing operations were conducted at higher temperatures, the added cellulose seemed to stabilize the effect of time on the workability of the matrix, resulting in a less significant torque decline compared to that of the matrix.…”
Section: Resultsmentioning
confidence: 99%
“…Consequently, during the mixing, a greater number of collisions between aggregates/agglomerates could be determined, leading to fiber deterioration [ 21 ] or even re-agglomeration phenomena [ 22 ]. It can be concluded that, at lower processing temperatures, the introduction of a greater amount of fibers determines a higher instability, physically linked to the efficiency in their incorporation into the polymer matrix [ 23 ]. However, if the mixing operations were conducted at higher temperatures, the added cellulose seemed to stabilize the effect of time on the workability of the matrix, resulting in a less significant torque decline compared to that of the matrix.…”
Section: Resultsmentioning
confidence: 99%
“…19 This is the main explanation for the dependence of stabilization torque on the load of the fiber in the BM, as observed in similar mixer studies. 3,20 As for the polymer content, the stabilization torque turned out to be lower when the mixture of polymers in the formulation was richer in PLA.…”
Section: Developing Statistical Modelsmentioning
confidence: 98%
“…2 High-density polyethylene (HDPE), which has a low melting temperature (135 C), is the most widely used polymer in the wood-plastic composite industry. 3 Biopolymers are an alternative or complement to synthetic polymers and are considered green polymers due to their renewable base and biodegradability. 4 Polylactic acid (PLA) and thermoplastic starch are biodegradable polymers widely used as components of BMs.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Research on the subject is quite mature, dating back to at least 80 years ago, with several products reaching the market over the past decades. Currently, research on the subject focuses mostly on technical aspects, such as optimization of processing parameters and formulation, 768,769 public perception and market acceptance, 770…”
Section: Aymentioning
confidence: 99%